Science-policy interfaces for sustainable climatesmart agriculture uptake: lessons learnt from national science-policy dialogue platforms in West Africa - Zougmoré, Robert B.; Partey, Samuel T.; Totin, Edmond; Ouédraogo, Mathieu; Thornton, Philip K.; Karbo, Naaminong; Sogoba, Bougouna; Dieye, Bounama; Campbell, Bruce M. (Informa UK Limited, 2019)
Connecting science with policy has always been challenging for both scientists and policymakers. In Ghana, Mali and Senegal, multi-stakeholder national science-policy dialogue platforms on climate-smart agriculture (CSA) were setup to use scientific evidence to create awareness of climate change impacts on agriculture and advocate for the mainstreaming of climate change and CSA into agricultural development plans. Based on the platforms’ operations and achievements, we used semi-structured questionnaire interviews and reviewed technical reports produced by the platforms to analyse how their modes of operation and achievements improve understanding of the science-policy interfaces between agricultural and climate change decision making. Results showed that these platforms constitute an innovative approach to effectively engaging decision-makers and sustainably mainstreaming climate change into development plans. Effective science-policy interaction requires: (a) institutionalizing dialogue platforms by embedding them within national institutions, which improves their credibility, relevance and legitimacy among policymakers; (b) two-way communication, which contributes substantially to the co-development of solutions that address climate change vulnerabilities and impacts; and (c) relevant communication products and packaging of evidence that aligns with country priorities, which facilitates its uptake in policy-making processes. We conclude with a framework of sustainable operation for such platforms based on lessons learnt in the three countries.